El pago de las obligaciones y responsabilidades de las pensiones alimenticias de los obligados subsidiarios y su incidencia en el aspecto socio económico, jurídico y de derechos - SARANGO SARANGO, LUZ EMERITA (2016)
I have developed this legal research work in the legal field of public law, specifically in the flaws that exist in the organic code of childhood and adolescence, in relation to the required subsidiary. In the Code Organic of Childhood and Adolescence of our Ecuadorian legislation has been established in its article 130 obligation of the provision of food by the way type of people, when the father is not able to do so, they are forced, grandparents, brothers and uncles, many of these families have not even for their own food, as well as having to put aside her own children to care for your child or grandchild as the case may be. In addition to infringing the rights established in article 35 of the Constitution of the Republic the Ecuador which establishes them as groups of priority attention by the need of that the judge at the time of resolve must take into account elements to determine the economic conditions of the subsidiary liable, since many times does not have the conditions necessary to solve the food provision therefore forcing them to comply with the payment of alimony and to be considered vulnerable is violating your rights, please see the need for reforms to the Code Organic of Childhood and Adolescence established standards less invasive to the required subsidiary rights especially for older adults. In which we used descriptiva-propositiva methodology; because it is necessary to describe, compare and verify the facts, phenomena, and index cards, tabs nemotecnicas in order to collect doctrinal information, consultations and 5 analysis of documentary sources, with the purpose of broadening and deepening information based on information reported by the media circumstances of legal nature arising around the object of study and work, and based on the retrieved results reaching conclusions and recommendations raised, and on this basis I present the proposed legal reform in which I Express it must be reformed the Code Organic of Childhood and Adolescence exonerating the forced payment of alimony, leaving as a rarity, when proven permanent physical or mental inability to work by the principal or in case of death.